Kosovo : Poverty Assessment, Volume 1. Main Report - World Bank (Washington, DC, 2013)
As Kosovo goes beyond the emergency relief phase, taking into consideration the situation of those that the conflict has left behind is vital to the effectiveness of any strategy for economic development. The study is designed to inform the current policy debate in the area of poverty alleviation, and social service delivery, and to include these in the Joint Interim Administrative Structure (JIAS), the World Bank, and other donors perspectives. Within the definition of poverty as a multidimensional force that extends beyond low levels of income, the report covers a wide range of issues, including consumption, income, education, health, and social protection. It is predominantly based on data from the Living Standard Measurement Survey, statistically representative of both the Albanian, and Serb population, though not of other ethnic groups. The study comprises two volumes, the first one reviews background information, and data to examine the extent of poverty in Kosovo, the role of food aid, and identifies the correlates of extreme poverty. Poverty is analyzed versus income sources, and social assistance, and against inequality in educational attainments, and access to health care, to lay the foundation for building a strategy for poverty alleviation. Based on the profile of poverty in Kosovo, the second volume discusses the consumption poverty profile, and factors affecting the risk of extreme poverty, to challenge building an effective social protection strategy. Conclusions indicate that to avoid an increase in poverty, economic growth should increase the share of income derived from wages, and the JIAS must increase assistance to households not able to participate in the economy.